Improving anaerobic digestion via direct interspecies electron transfer requires development of suitable characterization methods. (June 2019) - Van Steendam, Caroline; Smets, Ilse; Skerlos, Steven; Raskin, Lutgarde
Graphical abstract: Highlights: Many recent AD studies mistakenly link performance improvements exclusively to DIET. Unequivocally proving the occurrence of DIET requires a complex set of methods. This paper groups DIET characterization methods in four categories and discusses their strengths and weaknesses. This paper presents promising DIET detection approaches that merit further exploration. Abstract : Recent anaerobic digestion studies commonly attribute performance improvements (e.g. increased methane production, enhanced process stability, reduced startup times) to direct interspecies electron transfer (DIET), even though only indirect evidence of DIET is available and DIET alone does not explain enhanced performance in many cases. This review evaluates methods believed to confirm the occurrence of DIET in anaerobic systems. 16S rRNA gene sequencing and meta-omics approaches are necessary to further DIET knowledge but are limited in their ability to confirm the occurrence of DIET. In situ use of cyclic voltammetry should be explored further, as well as microscopy and image analysis procedures to quantify stained cytochromes. Furthermore, linking interspecies distance, interspecies mixing, and cellular activity to a DIET-based electron transfer model is promising but needs further validation for anaerobic digestion systems. In short, a combination of methods is necessary to confirm the occurrence and expand our knowledge of DIET.